Bleeding and sedimentation of cement paste measured by hydrostatic pressure and Turbiscan. (February 2017) - Peng, Y.; Lauten, R.A.; Reknes, K.; Jacobsen, S.
Abstract: Sedimentation and bleeding of cement pastes with lignosulfonate were studied by visual observation, HYdroStatic Pressure Test (HYSPT) and Turbiscan measurements showing two bleeding stages: a fast initial phase followed by a phase with diminishing sedimentation rate. A turbid bleeding zone establishes during the fast bleeding phase and the top layer gradually becomes transparent in the diminishing phase within minutes or hours depending on admixture and solid fraction. The bleeding rates measured visually and by HYSPT in the first 2 h are higher than the ones calculated by Kozeny-Carman Equation, whereas turbiscan shows lower rates. Both HYSPT and Turbiscan monitor the particle and fluid fluxes and thus describe bleeding from turbid to clear zone respectively by observing the density variation of bulk paste or the change in optical density of the surface region. Lignosulfonate reduces bleeding by improving particle dispersion to various degrees depending on types and dosages.